Intergrated metabonomic study of the effects of Guizhi Fuling capsule intervention on primary dysmenorrheal using RP‐UPLC–MS complementary with HILIC‐UPLC–MS technique. (2nd October 2017) - Lang, Lang; Meng, Zhaorui; Sun, Lan; Xiao, Wei; Zhao, Longshan; Xiong, Zhili
Abstract: Guizhi Fuling capsule (GFC), developed from the traditional Chinese prescription of Guizhi Fuling Wan, has been commonly used for the treatment of primary dysmenorrhea (PD). However, the intervention effective mechanism in vivo has not been well elucidated. In this study, an integrated plasma metabonomic strategy based on RP‐UPLC‐MS coupled with HILIC‐UPLC‐MS technique has been developed to investigate the global therapeutic effects and intervention mechanisms of GFC on dysmenorrhea rats induced by oxytocin. The 20 potential biomarkers were identified and primarily related to sphingolipid metabolism, steroid hormone biosynthesis, glycerophospholipid metabolism, amino acid metabolism, lipid metabolism and energy metabolism. The results showed that the GFC has therapeutic effects on rats with dysmenorrhea via the regulation of multiple metabolic pathways. Some new potential biomarkers associated with primary dysmenorrhea such as phenylalanine, tryptophan, taurine, carnitine, betaine, creatine and creatinine have been discovered in this study for the first time. This study provides a metabonomic platform based on RP‐UPLC‐MS complementary to HILIC‐UPLC‐MS technique to investigate both nonpolar and polar compounds, so as to get a more comprehensive metabolite information to yield insight into the pathophysiology of PD and assessing the efficacy of GFC on PD rats.